Calculation of Cracks in Partially Steel Fiber Reinforced Concrete Beams with BFRP Bars - Wei Shen; Shengping Chen; Jianbo Zhang (Advances in Materials Science and Engineering)
The effects of steel fiber volume rate and steel fiber concrete thickness on the crack development and crack resistance of basalt fiber reinforced polymer (BFRP) beams were investigated by flexural tests on six partially reinforced BFRP steel fiber reinforced concrete beams. The results showed that the addition of steel fibers effectively limited the extension height of the initial crack and the crack expansion after cracking, and the difference in the extension height of the crack between the partial steel fiber test beam and the full-section steel fiber test beam was small. For BFRP reinforced concrete beams partially reinforced with steel fibers, the development of the maximum crack width can be effectively suppressed under ultimate load. Its crack arresting effect is more similar to that of full-section steel fiber reinforced concrete beams with BFRP bars; it shows that adding steel fibers only in the compression zone of the beam can not only improve the load capacity of the beam but also obtain good economic benefits. According to the test results, on the basis of the bond-slip theory and the no-slip theory, a comprehensive calculation method of the crack spacing considering the bond effect between the steel bar and the concrete and the influence of the concrete protective layer is proposed. According to the calculation formula of crack width, and according to the influence of the actual plastic deformation of concrete in the tensile area of the section, the calculation formula of the normal section crack resistance of BFRP reinforced steel fiber concrete beams is carried out, and the calculation results are compared with the test results, which are in good agreement.